(untitled) (European Journal of Marketing and Economics, 2025)
The transition to urban electromobility faces significant challenges in regions with underdeveloped public transport infrastructure. This study investigates how service innovation can drive economically sustainable adoption by integrating technical solutions with stakeholder collaboration and user engagement. Through a systemic-relational framework, we collaborated with municipalities, industry partners, and academic institutions to develop and test solutions across four critical dimensions: (1) scalable charging infrastructure, (2) innovative business models, (3) multi-actor coordination mechanisms, and (4) socio-cultural acceptance strategies. A case study in a mid-sized German city demonstrates that combining technical deployment with value-added services not only reduces operational costs but also unlocks new revenue streams and shifts mobility behaviors. A key finding is the "flow factor"—emotional engagement through experiential marketing and user-centric design—which significantly boosts adoption rates and usage intensity. Our analysis highlights the necessity of aligned policy incentives, strategic investment frameworks, and cross-sector partnerships to build resilient electromobility ecosystems. The paper concludes with actionable recommendations for policymakers and industry leaders to accelerate sustainable urban mobility through service-driven innovation.